Detection of cell-free histones in the cerebrospinal fluid of pediatric central nervous system malignancies by imaging flow cytometry - Buzova, Diana; Frohlich, Jan; Zapletalova, Danica; Raffaele, Marco; Lo Re, Oriana; Tsoneva, Desislava K.; Sterba, Jaroslav; Cerveny, Jan; Vinciguerra, Manlio (Frontiers in Molecular Biosciences, 2023)
Introduction: Pediatric brain tumours (PBT) are one of the most common malignancies during childhood, with variable severity according to the location and histological type. Certain types of gliomas, such a glioblastoma and diffuse intrinsic pontine glioma (DIPG), have a much higher mortality than ependymoma and medulloblastoma. Early detection of PBT is essential for diagnosis and therapeutic interventions. Liquid biopsies have been demonstrated using cerebrospinal fluid (CSF), mostly restricted to cell free DNA, which display limitations of quantity and integrity. In this pilot study, we sought to demonstrate the detectability and robustness of cell free histones in the CSF. Methods: We collected CSF samples from a pilot cohort of 8 children with brain tumours including DIPG, medulloblastoma, glioblastoma, ependymoma and others. As controls, we collected CSF samples from nine children with unrelated blood malignancies and without brain tumours. We applied a multichannel flow imaging approach on ImageStream(X) to image indiviual histone or histone complexes on different channels. Results: Single histones (H2A, macroH2A1.1, macroH2A1.2 H2B, H3, H4 and histone H3 bearing the H3K27M mutation), and histone complexes are specifically detectable in the CSF of PBT patients. H2A and its variants macroH2A1.1/macroH2A1/2 displayed the strongest signal and abundance, together with disease associated H3K27M. In contrast, mostly H4 is detectable in the CSF of pediatric patients with blood malignancies. Discussion: In conclusion, free histones and histone complexes are detectable with a strong signal in the CSF of children affected by brain tumours, using ImageStream(X) technology and may provide additive diagnostic and predictive information.